Exploratory Analysis of Gene Expression Patterns in Chemotherapy-Treated Colorectal Cancer Patients - Farooq, Mustafa Ayad; Jumaah, Hind Mahmood; Alwan, Israa Ayoub (American Journal of Biology and Natural Sciences, 2025)
CRC remains to be one of the major causes of death by cancer all over the world and metastatic CRC poses a challenge in both treatment and prognosis because of heterogeneity of the tumors and resistance to drugs. The authors investigated the profile of gene expression differences in 21 patients who received chemotherapy with 5-fluorouracil, oxaliplatin, and irinotecan, with CRC. By means of principal component analysis and hierarchical clustering, it was possible to find out specific molecular subgroups, which unveiled the most important genes that exhibited high expression variations. These results give an understanding of the molecular dynamics of the development of tumors and response to treatment in CRC. The identified gene signatures can be considered as prospective prognosis biomarkers and targets of personal treatment. To continue this line of study, future-oriented research ought to concentrate on functional confirmation of the individual genes and their harmonization with the multi-omics data to improve precision medicine in CRC.